DIGITAL TRANSFORMATION IN EDUCATION SYSTEMS (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
Digital transformation is fundamentally changing education systems around the world by integrating advanced information technologies into teaching, learning, and administration. This article explores the adoption of digital tools, cloud computing, artificial intelligence, and online learning platforms in modern education. It examines how these technologies improve accessibility, engagement, personalization, and operational efficiency. The study also considers the challenges associated with infrastructure, digital literacy, data security, and equity. Overall, the implementation of digital solutions enhances student learning outcomes, supports institutional management, and prepares educational institutions for the evolving demands of the digital era.